Active management of the third stage of labor with and without controlled cord traction: a systematic review and meta‐analysis of randomized controlled trials. (9th June 2014) - Du, Yongming; Ye, Man; Zheng, Feiyun
Abstract Objective To determine the specific effect of controlled cord traction in the third stage of labor in the prevention of postpartum hemorrhage. Data sources We searched PubMed, Scopus and Web of Science (inception to 30 October 2013). Study selection Randomized controlled trials comparing controlled cord traction with hands‐off management in the third stage of labor were included. Results Five randomized controlled trials involving a total of 30 532 participants were eligible. No significant difference was found between controlled cord traction and hands‐off management groups with respect to the incidence of severe postpartum hemorrhage (relative risk 0.91, 95% confidence interval 0.77–1.08), need for blood transfusion (relative risk 0.96, 95% confidence interval 0.69–1.33) or therapeutic uterotonics (relative risk 0.94, 95% confidence interval 0.88–1.01). However, controlled cord traction reduced the incidence of postpartum hemorrhage in general (relative risk 0.93, 95% confidence interval 0.87–0.99; number‐needed‐to‐treat 111, 95% confidence interval 61–666), as well manual removal of the placenta (relative risk 0.70, 95% confidence interval 0.58–0.84) and duration of the third stage of labor (mean difference −3.20, 95% confidence interval −3.21 to −3.19). Conclusions Controlled cord traction appears to reduce the risk of any postpartum hemorrhage in a general sense, as well as manual removal of the placenta and the duration of the third stage of labor. However, the reduction in the occurrence of severe postpartum hemorrhage, need for additional uterotonics and blood transfusion is not statistically significant.